Diagnosis and treatment of type B insulin resistance syndrome complicated by mixed connective tissue disease: a case report and literature review - HUANG Yu, CUI Yuliang, LIU Jing (Zhenduanxue lilun yu shijian, 2025)
This study reports a case of type B insulin resistance syndrome (TBIRS) complicated by mixed connective tissue disease. The patient, a 54-year-old male diagnosed with mixed connective tissue disease, exhibited symptoms including polyuria, dry mouth, polydipsia, continuous weight loss, hyperglycemia, and acanthosis nigricans. Laboratory tests confirmed insulin resistance and hyperinsulinemia, leading to a final diagnosis of TBIRS. The patient was treated with glucocorticoids, hydroxychloroquine, and insulin sensitizer. After two weeks, the patient showed improvement in polyuria, dry mouth, and polydipsia, with stable blood glucose levels. One month later, the patient's acanthosis nigricans improved, weight stabilized, and blood glucose levels remained stable. TBIRS is an autoimmune disease, more commonly seen in middle-aged females. The majority of cases present with hyperglycemia and hyperinsulinemia, while hypoglycemia is rare. Diagnosis is primarily based on clinical manifestations, and treatment plans should be tailored according to the symptoms and associated autoimmune diseases. TBIRS is often associated with systemic lupus erythematosus. However, this case reported in this study presents a rare instance of TBIRS with mixed connective tissue disease. The prognosis for TBIRS patients is poor, with a high mortality rate. Early diagnosis and treatment can help improve outcomes. In this case, a novel insulin sensitizer chiglitazar sodium was used for blood glucose control for the first time, demonstrating good hypoglycemic efficacy. The combined use of immunosuppressive agents proved effective, providing important guidance for early detection and precise treatment of such diseases in clinical practice.